Improving Children's Literacy Development Through Puppet Letter Media in Group B - Fitrawati, Hesti; Asnawati, Asnawati; Pebriani, Ela (Journal Of Dehasen Educational Review, 2023)
The purpose of this study was to determine whether through the media puppet letters can improve children's literacy development in Group B at PAUD IKI PTPN 07 Seluma Regency. Classroom Action Research (PTK) which is focused on the classroom situation, or commonly known as classroom action research, the procedure used is in the form of a cycle. The main subject in this study was group B children totaling 15 children at PAUD IKI PTPN 07 Seluma Regency. This Classroom Action Research uses the Jhon Elliot model where each cycle consists of four main activities, namely planning, implementation, observation, and reflection carried out through two cycles, namely cycle I and II. Data collection techniques used observation and documentation methods. Data analysis was carried out descriptively qualitative-quantitative with the emphasis used to determine the improvement of the process expressed in a predicate, while quantitative data analysis was used to determine the improvement of results using percentages. The results of improving children's literacy development through letter puppet media in Group B at PAUD IKI PTPN 07 Seluma Regency in cycle I meeting I amounted to 56% and meeting II amounted to 75%. In cycle II meeting I found an increase of 90%. The conclusion of the research is that through letter puppet media, the development of children's literacy in Group B at PAUD IKI PTPN 07 Seluma Regency is improved. Evidently in cycle II there was a significant increase, the percentage of achievement was 90% with very good developing criteria (BSB).